Signal Transduction of Sphingosine-1-Phosphate G Protein—Coupled Receptors - Nicholas Young; James R. Van Brocklyn (The Scientific World Journal)
Sphingosine-1-phosphate (S1P) is a bioactive lipid capable of eliciting dramatic effects in a variety of cell types. Signaling by this molecule is by a family of five G protein—coupled receptors named S1P1–5 that signal through a variety of pathways to regulate cell proliferation, migration, cytoskeletal organization, and differentiation. These receptors are expressed in a wide variety of tissues and cell types, and their cellular effects contribute to important biological and pathological functions of S1P in many processes, including angiogenesis, vascular development, lymphocyte trafficking, and cancer. This review will focus on the current progress in the field of S1P receptor signaling and biology.